Continuous Monitoring of Blood Pressure Using a Wrist-Worn Cuffless Device. (16th February 2022) - Sayer, Gabriel; Piper, Greta; Vorovich, Esther; Raikhelkar, Jayant; Kim, Gene H; Rodgers, Daniel; Shimbo, Daichi; Uriel, Nir
Abstract: BACKGROUND: Measuring an accurate blood pressure (BP) in ambulatory patients is critical for therapeutic decisions. An accurate noninvasive device that measures BP continuously could provide a more comprehensive assessment of BP. The aim of this study was to determine whether the LiveOne device, a cuffless wristband that provides continuous BP measurements, is accurate in comparison to an invasive arterial line (A-line). METHODS: We enrolled hospitalized patients and healthy volunteers in this multicenter study. All patients had an invasive A-line. Waveforms were simultaneously downloaded from the A-line and LiveOne device. The primary outcome was the correlation between the LiveOne device and the A-line for systolic BP (SBP) and diastolic BP (DBP). RESULTS: Thirty-four patients with 233 measurement periods were included. Mean age was 60.7 ± 15.2 years, and 15 (44%) were female. The correlation for SBP was 0.91 and for DBP was 0.85. The mean band error was 0.0 ± 6.9 mm Hg for SBP and 1.2 ± 5.7 mm Hg for DBP. The mean absolute error was 8.2 ± 5.8 mm Hg for SBP and 6.4 ± 3.9 mm Hg for DBP. For SBP, 98% of LiveOne measurements were within 15 mm Hg and for DBP, 92% of LiveOne measurements were within 10 mm Hg. CONCLUSIONS: The LiveOne device provides continuous, noninvasive BP measurements that are accurate in comparison to A-line measurements. The portability and unobtrusive nature of this device and the ability to provide continuous BP measurements may offer advantages over currently available BP monitors. CLINICAL TRIALS REGISTRATION: Trial Number NCT03919136. Graphical Abstract: